2016
DOI: 10.1007/s13197-016-2342-5
|View full text |Cite
|
Sign up to set email alerts
|

Semi-industrial microwave treatments positively affect the quality of orange-colored smoothies

Abstract: Thermal processing extends the shelf life of fruit and vegetables products by inactivating microorganisms and enzymes. The effect of a pasteurization (P) treatment, 90 ± 2°C for 35 s, provided by continuous semi-industrial microwave (MW) under different conditions (high power/ short time and low power/long time) or conventional pasteurization (CP) on orange-colored smoothies and their changes throughout 45 days of storage at 5°C were investigated. Results indicated that vitamin C and antioxidant capacity (FRAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Overall, MWH systems have been considered to deliver reduced thermal exposure to inactivate microorganisms (Arjmandi and others ). However, some studies reported: (1) the inactivation of natural microorganisms in tomato juice (Stratakos and others ) and in pomegranate juice (Dhumal and others ); (2) a 3 log reduction of bacteria and fungi population in many juice blends (Math and others ); and (3) the microbial stability during storage of guava nectar (Salazar‐González and others ) and orange juice (Demirdöven and Baysal ).…”
Section: Thermal Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, MWH systems have been considered to deliver reduced thermal exposure to inactivate microorganisms (Arjmandi and others ). However, some studies reported: (1) the inactivation of natural microorganisms in tomato juice (Stratakos and others ) and in pomegranate juice (Dhumal and others ); (2) a 3 log reduction of bacteria and fungi population in many juice blends (Math and others ); and (3) the microbial stability during storage of guava nectar (Salazar‐González and others ) and orange juice (Demirdöven and Baysal ).…”
Section: Thermal Treatmentsmentioning
confidence: 99%
“…Recently, MWH successfully eliminated vegetative bacteria in smoothies without compromising food quality. Interestingly, L. monocytogenes was not detected throughout the shelf life of product (Arjmandi and others ). Since increasing MWH power has an important effect on the reduction of heating time, a combination of high power and short time might be a solution for reducing the loss of quality, as well as destroy harmful pathogenic microorganisms (Arjmandi and others ).…”
Section: Thermal Treatmentsmentioning
confidence: 99%
“…In the study of Igual et al (2010) , MW treatment (45 W/mL, 30 s) and conventional heating (80 °C, 11 s) caused a similar decrease of total phenolic content (34.64%) and % DPPH (40%), but MW treated grapefruit juices better preserved total phenolic and antioxidant capacity when compared with fresh or conventional pasteurised ones during storage. Arjmandi et al (2016) reported that the maximum total phenolic was obtained in semi-industrial MW treated orange-colored smoothies (1.0–18 w/mL, 93–646 s) without significant differences among MW treatments. Meanwhile the loss of antioxidant capacity was only 5% under the combination of high power/short time, and the value was 28% of that observed in conventional pasteurization (90 °C, 35 s) sample ( Arjmandi et al, 2016 ).…”
Section: Resultsmentioning
confidence: 97%
“…Another promising non-conventional thermal treatment of fruit and vegetable juices is the microwave heating (MWH). This way presents some benefits, like the reduced processing time, high power efficiency and a good process control for reducing the loss of juices quality as well as destroy harmful pathogenic bacteria [70]. Overall, the effectiveness of MWH as compared to the traditional treatment is confirmed by: the high total phenols and flavonoid compounds in watermelon, black jamun, litchi, grapefruit and pineapple juices [71]; the preservation of physicochemical properties in tomato juice [72] and many juice-blends [73]; the significant retention of ascorbic acid and the preservation of color and rheological properties in guava nectar [74].…”
Section: Alternative Physical Treatmentmentioning
confidence: 99%